Catland : Louis Wain and the great cat mania - Hughes, Kathryn, 1959- (Johns Hopkins University Press, 2024)
In Catland, Kathryn Hughes chronicles the cat craze of the early twentieth century through the life and career of Louis Wain. Wain's anthropomorphic drawings of cats in top hats falling in love, sipping champagne, golfing, driving cars, and piloting planes are some of the most instantly recognizable images from the era. His round-faced fluffy characters established the prototype for the modern cat, which cat "fanciers" were busily trying to achieve using their newfound knowledge of the latest scientific breeding techniques. Despite being a household name, Wain endured multiple bankruptcies and mental breakdowns, spending his last fifteen years in an asylum, drawing abstract and multicolored felines. But it was his ubiquitous anthropomorphic cats that helped usher the formerly reviled creatures into homes across Europe. -- adapted from jacket